Estratégias de propagação de barueiro (Dipteryx alata Vog.) e jatobazeiro do cerrado (Hymenaea stigonocarpa MART) - Larson, Léia Carla Rodrigues dos Santos [UNESP] (2014)
Brazilian native species should be preserved and researched for maintenance and perpetuation of origin in your biome. Generally, the native fruits are sources of income generation for the local population, because their many uses in food and feed, as well as social and environmental interests. Among the various native fruit species include the barueiro and jatobazeiro and which can be used as wood, seeds, pulp, resin, and the sheets may also be part of a production system as farming areas. However, the exploitation of jatobazeiro and barueiro may not occur only through predatory extraction, should be deployed commercially, due to seasonal production and consumer demand. However, to maximize the use of predatory native forest species, propagation and cultivation techniques should be investigated, since seed production does not occur throughout the year, and many seeds have various types of dormancy. It is important to know the best method of propagation of these species for seedling production and adaptation in different types of soils or substrates nutritions. Thus, the aim of this work was to produce seedlings and barueiro jatobazeiro on different types of substrates and develop protocols for micropropagation of the baru. It was possible to verify that the pure soil was the best seedling development, and that liming and mineral fertilization provided increased growth of seedlings. The manure applied to the substrate did not benefit seedling production of species, because the excess of some nutrients, which caused a nutritional imbalance. The baru can be micropropagated in the laboratory, and their seeds germinated in vitro